The Purchase of Souvenirs of the Police Tero Football Club Fans - Kulwanich, Anuchit; PiromKam, Bunjob; Potimoo, Kittipong (Journal of Innovation and Management, 2020)
The purpose of this research was to study the level of buying souvenirs, fans, football clubs and compare the selection of Police Tero football club fans' souvenirs classified by personal status information. By quantitative research method. The sample group consisted of 320 fans who watched football matches using systematic sampling. The tools used were questionnaires. The research found that 1) Fans of the Police Tero football club team found that buying a souvenir of the Police Tero football club fans in the overall picture has a high level of opinion. When considering each aspect with the highest average value in terms of products and marketing promotion, followed by distribution channels and the lowest mean value is the price, respectively and 2) comparison of the selection of souvenirs for the Police Tero football club fan club found that Police Tero football club fans have opinions on products such as gender, age, marital status, education level. The difference was statistically significant at the level of .05. The price was the gender, marital status, and the statistical significance at the level of .05. Distribution channels were different occupation, with statistical significance at the level of .05. And marketing promotion, which is gender, age, marital status, income, and statistical significance at the level of .05.